Digital transformation, labour share, and industrial heterogeneity - Nanxu Chen; Dongqing Sun; Jing Chen (Journal of Innovation & Knowledge (JIK), 2022)
For this study, we examined the relationship between the digital economy and labour share from the perspective of industrial heterogeneity. To analyse the digital economy's impact on labour share, we introduced a digital economy into a framework concerning labour share. We then built a mathematical model describing the influencing mechanism of the digital economy on labour share. We generated data from Chinese listed enterprises (n=3778) from 2007 to 2019 and applied a two-way fixed effects model to scrutinise the data. The results show that (1) the digital economy affects labour share through three countervailing forces: the productivity improvement effect, factor-biased effect, and scale return change effect; (2) the labour share would change to -0.12%, 0.36%, and -0.48% through the productivity improvement effect, factor-biased effect, and scale return change effect, respectively, with a 0.1% increase in the digital economy, indicating that the labour-biased effect is the main component of the increase in labour share, and the scale return effect is the primary source of the decline in labour share; (3) a phenomenon similar to the digital divide exists in the factor-biased and scale return change effects for heterogeneous industries. Theoretically and empirically, this study contributes to the existing findings and offers useful managerial insights.
Keywords: 650; Digital divide; Digital economy; Industrial heterogeneity; Labour share